Novel Method Enabling the Use of Cryopreserved Primary Acute Myeloid Leukemia Cells in Functional Drug Screens. Issue 7 (October 2017) - Degnin, Michelle; Agarwal, Anupriya; Tarlock, Katherine; Meshinchi, Soheil; Druker, Brian J.; Tognon, Cristina E.
Abstract : The ability to assess antileukemic drug activity on primary patient samples is a powerful tool in determining potential drug targets and selection of therapeutic agents with biological and functional rationale. We previously established small molecule inhibitor screens for use on freshly isolated leukemia cells for this purpose. Here we describe a method that produces functional small molecule inhibitor screening results using cryopreserved primary acute myeloid leukemia cells. This method was established to take advantage of biorepositories containing archival material, such as those established by the Children's Oncology Group, and to enable validation of potential pathway dependencies uncovered by genomic analysis. Various conditions used to thaw and culture cryopreserved specimens were assessed for effect on viability, differentiation, and the ability to recapitulate sensitivity results obtained on fresh samples. The most reproducible results were obtained by quick-thawing and culturing samples in cytokine rich media before performing drug screens. Our data suggest that cytokine-enriched media aids in maintaining the viability and numbers required to perform functional analysis on cryopreserved leukemia cells. This method can aid in producing informative data on therapeutic targeting and precision medicine efforts in leukemia by making use of biorepositories and bio banks. Abstract : Supplemental Digital Content is available in the text.